2011
DOI: 10.1177/0266242611402565
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization of biotechnology start-ups: Geographic location and mimetic behaviour

Abstract: The objective of this article is to understand the extent to which location in a geographic cluster can explain international alliance formation. Geographic clusters are characterized by several dimensions: agglomeration economies, institutional forces and a manager’s mental models create the environment within the cluster. Therefore, to develop the research propositions, which were tested on a sample of US biotechnology start-ups, the study specifically analysed cluster size and firm competitive behaviour wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 60 publications
(100 reference statements)
1
14
0
1
Order By: Relevance
“…This finding supports institutional theorists who argue that SMEs tend to model themselves after competitors in their industry. Moreover, extending prior research (Delerue & Lejeune, 2012;Fernhaber & Li, 2010), our findings reveal that peers in a firm's network not only influence a young SME's general propensity to internationalize, but that imitative behavior is precise to the chosen internationalization mode.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding supports institutional theorists who argue that SMEs tend to model themselves after competitors in their industry. Moreover, extending prior research (Delerue & Lejeune, 2012;Fernhaber & Li, 2010), our findings reveal that peers in a firm's network not only influence a young SME's general propensity to internationalize, but that imitative behavior is precise to the chosen internationalization mode.…”
Section: Discussionsupporting
confidence: 83%
“…Previous research has for example investigated whether firms imitate certain types of alliances popular in their industry (Delerue & Lejeune, 2012;Yeniyurt, Townsend, Cavusgil, & Ghauri, 2009). However, research so far has less emphasized how exactly firms imitate internationalization patterns when exposed to a range of different internationalization patterns in their environment.…”
Section: Introductionmentioning
confidence: 99%
“…Fernhaber and Li (2013) found that older ventures benefit more from exposure to international alliance partners while younger ventures are more influenced by international exposure from geographically proximate firms; however, for new ventures, both types of network relationships positively influence their internationalization. Delerue and Lejeune (2012) argue, however, that being located in a geographic cluster in itself does not increase the probability of forming new international alliances; mimetic behavior among members of a cluster does. Other authors cast doubt on the ability of strategic alliances to influence early internationalization or the performance of smaller firms (Li et al 2012) but state that the different resources and competences the alliance furnishes may influence the internationalization process.…”
Section: International Strategic Alliances and International Entreprementioning
confidence: 90%
“…Pertinent literature on the biotechnology industry elucidates that clusters enhance the competitive advantage of the firms. SMEs in particular recognize the value of clustering in terms of developing increased foreign partnerships and of the additional exposure to global markets that comes with that [19,20].…”
Section: Impact On Clusteringmentioning
confidence: 99%